Unstructured large-eddy simulation for vehicle-components aerodynamics: flow over an idealised car mirror. (2nd September 2005) - Niceno, B.; Hanjalic, K.; Basara, B.
We present results of large-eddy numerical simulation (LES) of flow over an idealised car mirror using unstructured, cell-centred, colocated, finite volume solver. The 'mirror' consists of a wall mounted, backward facing semicylinder on which a hemisphere of diameter, two times larger was mounted. The considered Reynolds number of 330.000 corresponds to a realistic car velocity of 120 km/h. The simulation has been aimed at providing insight into the typical flow pattern around a car mirror, as well as for generating hydrodynamic inputs for computing noise generated by the mirror, and data for benchmarking industrial CFD for vehicle aerodynamics. The problem of specifying inflow conditions, which poses a serious challenge to LES, was overcome by simultaneous simulation of a segment of flow, upstream from the mirror, which was mapped in the spanwise direction to generate turbulence over the complete inflow cross section of the main flow domain. Because no experimental data are publicly available for this or similar configurations, the computations were performed for two numerical grids, a coarser with 500.000 and a finer with 1.000.000 cells. The results obtained with both grids agree well. Prior to LES of the mirror flow, the method was validated in LES of flow over a surface mounted cube in a matrix with different grids, as well as in some other flows, showing very good agreement with experiments.